Sexual Behavior in Teenagers Who Are Dating (Case Study of Junior High School "X" in Samarinda) - Fitri, Jusni Ananda; Rahayu, Eka Putri; Tonapa, Emelia; Hendriani, Dwi (Panakeia Journal of Epidemiology, 2024)
Abstract. Adolescence is a transition period from childhood to adulthood estimated at 13-16 years of age. Psychological changes cause sexual urges in adolescents. A reproductive health survey by the National Population and Family Planning Agency (BKKBN) in 2019, around 92% of adolescents who are dating, hold hands to kiss around 82%, and 63% of adolescents who are dating touch each other. This study aims to determine the sexual behavior of adolescents who are dating at SMP "X" Samarinda City. This research is a qualitative study with a case study research design and a descriptive approach using an in-depth interview method. The sampling technique used a purposive sampling technique which was carried out in Samarinda City on May 25 - July 25, 2023. The results of this study indicate that individual factors in the form of knowledge, attitudes, age and gender influence the sexual behavior of adolescents who are dating. The forms of sexual behavior of adolescents who are dating at SMP "X" Samarinda are holding hands, stroking hair, hugging and kissing.